2020
DOI: 10.3389/fphar.2020.00258
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Is Associated With Intestinal Microbiota Dysbiosis and Inflammation in a Brazilian Population

Abstract: Hypertension is a major global health challenge, as it represents the main risk factor for stroke and cardiovascular disease. It is a multifactorial clinical condition characterized by high and sustained levels of blood pressure, likely resulting from a complex interplay of endogenous and environmental factors. The gut microbiota has been strongly supposed to be involved but its role in hypertension is still poorly understood. In an attempt to fill this gap, here we characterized the microbial composition of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
77
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 105 publications
8
77
0
1
Order By: Relevance
“…The diverse collection of bacteria in the human gut microbiota contributes to several physiological functions by producing short chain fatty acids and vitamins (otherwise inaccessible to humans), regulating fat storage, promoting the differentiation of various cell types, protecting the host from colonization by pathogens, and creating tonic stimuli for the development/modulation of the immune system (76). On the other hand, any intestinal dysbiosis (disturbance in microbiota composition) is associated with the onset and/or aggravation of certain diseases including some autoimmune and allergic diseases, cancer, metabolic diseases, and bacterial infections (86)(87)(88)(89)(90). This crucial cross-talking between the human host and microbiota can be altered through dietary habits, influencing microbiota richness and diversity and potentially impacting intestinal barrier functions and the immune system (91,92).…”
Section: Role Of Microbiota and Dietary Antigens In The Development Omentioning
confidence: 99%
“…The diverse collection of bacteria in the human gut microbiota contributes to several physiological functions by producing short chain fatty acids and vitamins (otherwise inaccessible to humans), regulating fat storage, promoting the differentiation of various cell types, protecting the host from colonization by pathogens, and creating tonic stimuli for the development/modulation of the immune system (76). On the other hand, any intestinal dysbiosis (disturbance in microbiota composition) is associated with the onset and/or aggravation of certain diseases including some autoimmune and allergic diseases, cancer, metabolic diseases, and bacterial infections (86)(87)(88)(89)(90). This crucial cross-talking between the human host and microbiota can be altered through dietary habits, influencing microbiota richness and diversity and potentially impacting intestinal barrier functions and the immune system (91,92).…”
Section: Role Of Microbiota and Dietary Antigens In The Development Omentioning
confidence: 99%
“…Corroborating experimental data, a recent study identified a dysbiosis of the intestinal microbiota in hypertensive subjects, featured by reduced biodiversity and distinct bacterial signatures compared with the normotensive counterpart (Silveira-Nunes et al 2020). Along with a reduction in Bacteroidetes members, hypertensive individuals displayed increased proportions of Lactobacillus and Akkermansia and decreased relative abundances Roseburia and Faecalibacterium within the Lachnospiraceae and Ruminococcaceae families (Silveira-Nunes et al 2020). This study also reported an inflamed immune profile in hypertensive individuals with an increase in TNF/ IFN-γ ratio, and in TNF and IL-6 production when compared to normotensive subjects (Silveira-Nunes et al 2020).…”
Section: The Role Of the Immune System In Hypertension: A New Paradigmmentioning
confidence: 92%
“…In contrast, taxa from the Anaerostipes genus displayed a decreased abundance in this model (Bier et al 2018) indicating that beyond Lactobacillus genus, the dysbiosis of other genus and families may also be implicated in salt-induced hypertension. Corroborating experimental data, a recent study identified a dysbiosis of the intestinal microbiota in hypertensive subjects, featured by reduced biodiversity and distinct bacterial signatures compared with the normotensive counterpart (Silveira-Nunes et al 2020). Along with a reduction in Bacteroidetes members, hypertensive individuals displayed increased proportions of Lactobacillus and Akkermansia and decreased relative abundances Roseburia and Faecalibacterium within the Lachnospiraceae and Ruminococcaceae families (Silveira-Nunes et al 2020).…”
Section: The Role Of the Immune System In Hypertension: A New Paradigmmentioning
confidence: 94%
See 1 more Smart Citation
“…1 Diverse diets that contain increased levels of fiber, in contrast, afford a greater abundance of gut flora which may promote improved health. 2 Improving fiber consumption helps reverse some of the ill effects of the Western diet, 3 but the specific role of gut microbes in mediating disease states through fiber consumption has remained enigmatic. In a recent issue of Cell Host & Microbe, Glowacki and colleagues tackle this issue and demonstrate how a high-fiber diet can foster competitive colonization of specific microbes through a novel nutrient utilization pathway.…”
mentioning
confidence: 99%